THE REGULATORY REGULATION IN THE SPHERE OF COOPERATION OF CORRUPTION BY EMPLOYEES OF THE NATIONAL ANTI-CORRUPTION BUREAU OF UKRAINE - Єренко, Дмитро Віталійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the article deals with the genesis of the formation of corruption systems in the activities of officials of the National Anti-Corruption Bureau of Ukraine. The preconditions of the existence of corruption and their influence on modern relations in the activity of employees of the National Anti-Corruption Bureau of Ukraine are analyzed. Methods of research: using the dialectical method of cognition allowed to concentrate the accumulated scientific knowledge and practice of the use of anti-corruption legislation in the field of activity of officials of the National Anti-Corruption Bureau of Ukraine. Results: the preconditions for the emergence of corruption schemes and conflicts of interest in the area of employees of the National Anti-Corruption Bureau are determined. Discussion: the problem of eradicating corruption as a phenomenon, taking into account the current trends in the law of Ukraine.